METHODOLOGY FOR ASSESSMENT THE SUM OF CYBERSECURITY RISKS OF THE INFORMATION SYSTEM OF OBJECTS OF CRITICAL INFRASTRUCTURE - Honchar, Serhii; Potenko, Alexander (Ukrainian Information Security Research Journal, 2023)
To determine the economic feasibility of the application and selection of certain measures to handle the risk of the project as a whole, including both organizational and technical, it is necessary to make an estimated comparison of the cost of such measures with the maximum amount of losses resulting from several risks. The paper proposes a methodology for assessing the amount of cybersecurity risks of the information system of critical infrastructure facilities. The methodology proposed in the article is based on the application of methods for calculating the sum of risks and calculating complex risk. Based on the methodology proposed in this article, structural solutions of computing systems for assessing the risk of cybersecurity of information systems that implement methods for calculating the sum of risks and calculating complex risk are presented, as well as software systems are built. The results can be used to determine the risk of a complex project (there may be a complex information system), characterized by the consequences of the project and the likelihood of these consequences.